Numerical analysis of seismically induced liquefaction in earth embankment foundations. Part II. Application of remedial measures - Adalier, K; Aydingun, O (Canadian Science Publishing, 2003)
In Part I, a benchmark model without any liquefaction remediation countermeasure was considered and numerical results were compared with centrifuge experiment results. In Part II, three additional models with remediation are analyzed and compared with centrifuge experiments conducted on identical models. The countermeasures considered are densification of the sand layer by compaction, gravel berm surcharge, and sheet pile enclosure. In addition to comparing numerical results with experimental data for each model, the effect of each countermeasure relative to the benchmark model is also discussed. Insights into the dynamic behavior of the employed embankment-foundation and liquefaction countermeasure systems are provided. The results of this study show that computer simulation of earthquake effects on embankments with liquefiable foundations with and without several different retrofit measures is possible using data from conventional laboratory tests and a verified numerical procedure.
Keywords: liquefaction countermeasures; numerical modeling; coupled formulation; centrifuge; embankment; earthquakes